PEMBERIAN SANKSI REHABILITASI BAGI PENYALAHGUNA NARKOTIKA BERDASARKAN PASAL 127 DIKAITKAN DENGAN PASAL 103 UNDANG-UNDANG NOMOR 35 TAHUN2009 TENTANG NARKOTIKA - Thika Shalsabillah; Mukhlis R; Sukamarriko Andrikasmi (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2023)
In decision No. 1243/Pid.Sus/2022/PN.Sby the defendant was declared legallyand convincingly guilty of committing the crime of class I Narcotics abuse for himself.The Defendant was given a criminal sanction in the form of imprisonment for 2 (two)years but the Judge did not order or implement rehabilitation for the Defendant.Whereas in Article 127 paragraph (3) of Law No. 35 of 2009 clearly states that: